Strategi Pemasaran Program Jaminan Kecelakaan Kerja pada BPJS Ketenagakerjaan KC Meulaboh - Junaidi; Wiki Wijaya (Teewan Journal Solutions, 2025)
This study aims to analyze the marketing strategy of the Work Accident Insurance (JKK) program at BPJS Ketenagakerjaan KC Meulaboh. The focus of this research is to identify the marketing strategies used, assess their effectiveness in raising public awareness, and explore the challenges encountered in their implementation. The research method employed is a qualitative approach using in-depth interviews and documentation. The results indicate that the implemented marketing strategies include direct socialization to the community, community-based promotions, and social media campaigns. These strategies are quite effective in increasing public awareness, although challenges remain, such as a lack of understanding about the benefits of the JKK program and negative perceptions regarding its compliance with Sharia principles.